2017
DOI: 10.1093/bioinformatics/btx801
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for classifying tuberculosis drug-resistance from DNA sequencing data

Abstract: MotivationCorrect and rapid determination of Mycobacterium tuberculosis (MTB) resistance against available tuberculosis (TB) drugs is essential for the control and management of TB. Conventional molecular diagnostic test assumes that the presence of any well-studied single nucleotide polymorphisms is sufficient to cause resistance, which yields low sensitivity for resistance classification.SummaryGiven the availability of DNA sequencing data from MTB, we developed machine learning models for a cohort of 1839 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
132
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 16 publications
3
132
1
2
Order By: Relevance
“…Improvement in portable sequencing technology 60 and decreased cost of sequencing is promising to facilitate adoption in settings with lower resources were TB is most prevalent. However even if sequencing technology is available, our results suggest that genomic data interpretation will likely necessitate the use of statistical models or machine learning 16,58,61 given the number of genetic loci associated with resistance and the likely contribution of gene-gene interactions, especially if a quantitative prediction of the drug MIC is desirable 15 . The portability of the potential benefits of these advances to areas of the world where TB is most prevalent will require continued efforts in open sharing of data and analysis tools 62 .…”
Section: Para-aminosalicylic Acid (Pas)mentioning
confidence: 99%
“…Improvement in portable sequencing technology 60 and decreased cost of sequencing is promising to facilitate adoption in settings with lower resources were TB is most prevalent. However even if sequencing technology is available, our results suggest that genomic data interpretation will likely necessitate the use of statistical models or machine learning 16,58,61 given the number of genetic loci associated with resistance and the likely contribution of gene-gene interactions, especially if a quantitative prediction of the drug MIC is desirable 15 . The portability of the potential benefits of these advances to areas of the world where TB is most prevalent will require continued efforts in open sharing of data and analysis tools 62 .…”
Section: Para-aminosalicylic Acid (Pas)mentioning
confidence: 99%
“…Past studies utilizing whole genome sequencing have shown a wide range of performance, with sensitivities for first-line drugs ranging from 54% to 98% [8,12,13]. Second-line injectable drugs and fluoroquinolones had lower sensitivities, most of which were between 30% and 96% [8,12,13]. We hypothesize that the limited predictive performance of anti-tuberculosis drugs outside of first-line drugs could be improved using a large dataset enriched for resistance to second-line drugs and a more complex model.Deep learning models have become a powerful tool for many classification tasks.…”
mentioning
confidence: 93%
“…The limited scope of these tests suggests the need for a comprehensive antimicrobial susceptibility test.An alternative to targeted mutation detection methods is whole genome sequencing, which captures both common and rare mutations involved in drug resistance. Past studies utilizing whole genome sequencing have shown a wide range of performance, with sensitivities for first-line drugs ranging from 54% to 98% [8,12,13]. Second-line injectable drugs and fluoroquinolones had lower sensitivities, most of which were between 30% and 96% [8,12,13].…”
mentioning
confidence: 99%
“…To date, these methods have been restricted mostly to assign bacteria to 74 binary categories, i.e. susceptible or non-susceptible (12), (13), (14), (8), (15), (16), (17). 75 However, clinical breakpoints used to define susceptible and non-susceptible categories 76 can change and such binary categories do not allow following more subtle changes in 77 susceptibility in time.…”
Section: Introduction 48mentioning
confidence: 99%